Network usage determination using a transformer analogy. Issue 1 (1st January 2014) - Abdelkader, Sobhy M.; Morrow, David John; Conejo, Antonio J.
Abstract : This study presents a new method for determining the transmission network usage by loads and generators, which can then be used for transmission cost/loss allocation in an explainable and justifiable manner. The proposed method is based on solid physical grounds and circuit theory. It relies on dividing the currents through the network into two components; the first one is attributed to power flows from generators to loads, whereas the second one is because of the generators only. Unlike almost all the available methods, the proposed method is assumption free and hence it is more accurate than similar methods even those having some physical basis. The proposed method is validated through a transformer analogy, and theoretical derivations. The method is verified through application to the IEEE 30 bus system and the IEEE 118 test system. The results obtained verified many desirable features of the proposed method. Being more accurate in determining the network usage, in an explainable transparent manner, and in giving accurate cost signals, indicating the best locations to add loads and generation, are among the many desirable features.